The Integration of Islamic Psychology in the PAI Curriculum for Strengthening Student Character and Mental Health - Hidayah, Aulia Azizatul; Huda, Nuril (The Future of Education Journal, 2025)
This study explores the integration of Islamic Psychology into the Islamic Religious Education (PAI) curriculum as a strategic framework for strengthening students’ character and psychological well-being. In the face of globalization, digitalization, and social pressure, many students experience emotional instability and moral decline, highlighting the need for a holistic educational approach. The objective of this paper is to analyze the theoretical foundation and practical implications of integrating Islamic Psychology within PAI to develop a balanced educational paradigm encompassing cognitive, affective, and spiritual dimensions. Using a descriptive qualitative method through library research, this study reviews books, journal articles, and other relevant literature discussing Islamic education and character formation. The findings reveal four key insights: (1) Islamic Psychology provides a philosophical foundation for PAI to cultivate insan kamil, individuals who are intellectually, emotionally, and spiritually balanced; (2) PAI learning based on Islamic Psychology enhances students’ mental health through internalizing spiritual values such as sabr, syukr, tawakkal, and ikhlas; (3) integrative curriculum models reinforce character formation by uniting cognitive, affective, and psychomotor aspects; and (4) integration of Islamic Psychology fosters a holistic educational paradigm that restores the unity of knowledge, morality, and spirituality. In conclusion, integrating Islamic Psychology into the PAI curriculum serves as a transformative step toward building an education system that nurtures well-rounded, morally grounded, and mentally healthy individuals capable of facing modern challenges with spiritual resilience.